Prevalence and predictors of smoking cessation among smokers receiving smoking cessation intervention in primary care in Qatar: a 6-month follow-up study - Al-Dahshan, Ayman; Al Muraikhi, Hissa; Musa, Sarah; Joudeh, Anwar; Al Baker, Wadha; Selim, Nagah; Bougmiza, Iheb (Frontiers in Public Health, 2023)
Abstract Objective: To estimate the rate and predictors of smoking cessation in smokers attending ‎smoking cessation clinics in primary care settings in Qatar. ‎ Methods: A cross-sectional study was conducted among 759 smokers who had attended any of ‎the ten smoking cessation clinics in primary health care centers from January 2019 to June ‎‎2020. The sociodemographic, clinical, and smoking-related variables were assessed. Tailored ‎behavioral and pharmacotherapy were delivered, and patients were interviewed at 6 months to ‎estimate the 30-day point prevalence abstinence. To identify independent factors associated ‎with smoking cessation, a multivariable logistic regression analysis was performed.‎ Results: The mean age of participants was 40.6 (±11.3), majority being married, Arab and ‎employed, and having a tertiary education. Almost half of the smokers (48.7%) received ‎varenicline alone, ‎42.6‎% received NRT, and ‎31.8‎% received a combination of both. The ‎selection of drug therapy was based on ‎ preferences, experiences, and history of ‎previously ‎encountered adverse effects. ‎ The overall 30-day quit rate at six months follow-up was 32.4%. ‎About three-quarters (72.5%) of participants had at least one quit attempt and 12.5% had 3 or ‎more attempts. Later age at smoking ‎initiation, lower cigarette consumption at baseline, lower ‎CO concentration at ‎baseline, use of smoking cessation pharmacotherapy, ‎having made fewer ‎quit ‎attempts and non-exposure to ‎secondhand smoke among friends were identified as ‎significant predictors of successful quitting at six-months.‎ ‎Conclusion: The 30-day quit rate at six months follow-up (32.4%) is comparable to the ‎worldwide figure. However, further efforts should be made to plan cost-effective tobacco ‎dependence treatment taking into account predictors and at-risk groups.‎